Effectiveness of a Nurse-Led Educational Programme on Telemedicine Knowledge among Nursing Students in Dhaka - Chadayan, Chinna; Sweety, Melba Sahaya (Adult Health Nursing Journal, 2025)
ABSTRACTBackground: Telemedicine is transforming healthcare delivery, especially in underserved regions, by increasing access to care. Nursing students' knowledge of telemedicine is essential for preparing them for the evolving healthcare landscape.Objective: This study aimed to assess the effectiveness of a nurse-led educational program in enhancing nursing students' knowledge of telemedicine in Dhaka, Bangladesh.Methods: A quasi-experimental pre-test and post-test design was used with 40 nursing students who had no prior formal education in telemedicine. The intervention consisted of a 2-hour interactive session covering key concepts of telemedicine. Knowledge levels were measured using pre-test and post-test questionnaires. Data analysis involved paired t-tests to evaluate knowledge improvements.Results: Pre-test findings showed 67.5% of students had poor knowledge of telemedicine. After the intervention, 57.5% of students scored in the "Excellent" range, and only 2.5% scored in the "Poor" range. A paired t-test showed a significant increase in knowledge (p < 0.05).Conclusion: The nurse-led educational program significantly improved nursing students' knowledge of telemedicine. Age and gender were significant factors influencing knowledge scores, with older students and females performing better. The study recommends integrating telemedicine into nursing curricula to prepare future healthcare professionals.Keywords: Telemedicine, Nurse-led education, Nursing students, Knowledge improvement, Healthcare education, Tele-nursing.